Respuesta :

Answer:

[tex]f^{-1}(x)= \:\log _7\left(\left(8x-1\right)^3\right)[/tex]

Explanation:

[tex]f(x) = \frac{(7^x)^{\frac{1}{3} }+1}{8}[/tex]

Let f(x) be y

[tex]y = \frac{(7^x)^{\frac{1}{3} }+1}{8}[/tex]

exchange x and y

[tex]x = \frac{(7^y)^{\frac{1}{3} }+1}{8}[/tex]

simplify

[tex]8x= {(7^y)^{\frac{1}{3} }+1}[/tex]

simplify

[tex]8x - 1 = 7^{\frac{y}{3} }[/tex]

simplify

[tex]8x - 1 = \sqrt[3]{7^y}[/tex]

simplify

[tex](8x-1)^3 = 7^y[/tex]

apply log rules

[tex]y = \frac{log((8x-1)^3 )}{log(7)}[/tex]

[tex]y = \:\log _7\left(\left(8x-1\right)^3\right)[/tex]

therefore

[tex]f^{-1}(x)= \:\log _7\left(\left(8x-1\right)^3\right)[/tex]

ACCESS MORE